Launching a code of conduct - Freeman, Tami (Physics world, 2024)
Biomedical ethicist Vasiliki Rahimzadeh speaks to Tami Freeman about why the rapid growth of the commercial space sector makes it imperative that we develop a universal code of ethics for doing scientific research on human subjects in space.